The core-promoter factor TRF2 mediates a Fruitless action to masculinize neurobehavioral traits in Drosophila - Zahid Sadek Chowdhury (Nature Portfolio, 2017)
fruitless (fru) is an important sex-determinant gene that controls the expression of neuroanatomical sex differences in Drosophila. Here the authors report that a core-promoter factor, TRF2, suppresses a male-type neurite specification through direct interaction with FruBM isoform at the robo1 target gene promoter.